How Do Teachers Promote Honesty and Responsibility at the Elementary Education Level? A Narrative Inquiry - Muhammad Isro' Hidayatullah; Retna Ayu Rachmawati; Hamdiana Hamdiana; Lalu Sumardi; Zokhidova Rano Elbekovna; Lalu Mochamad Ridho Luthfi (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
In Indonesia, a crisis in moral and values education is emerging among elementary school students, posing a serious threat to the development of a superior generation if these values are not firmly instilled. The purpose of this study is to examine how teachers promote honesty and responsibility in their students. Using a narrative inquiry approach, the research explored teachers’ lived experiences to deepen understanding of how moral values are cultivated in elementary schools. The findings reveal that fostering honesty and responsibility is a long-term, ongoing process underpinned by consistent role modeling, empathy, and daily practice. Teachers emphasized that values are best instilled through example rather than instruction alone. Challenges include inconsistent implementation among educators, the influence of social media, and limited parental understanding. Nevertheless, teachers’ experiences highlight strategies such as culturally responsive practices, Classroom agreements, and restorative approaches that support more effective value formation. This study suggests expanding pedagogy toward moral pedagogy, positioning teachers as moral agents whose reflective experiences contribute to the development of contextual theory and practice. It is recommended that future research and curriculum design emphasize integrating honesty and responsibility through modeling, reflection, and collaboration among schools, families, and communities.